The Utilizing Instructional in Enhancing Students’ Listening Ability through Movie Report at Listening III - Luli Sari Yustina (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2016)
This paper is to discuss the utilizing instructional of movie report as one of the ways in enhancing student’s listening ability. Listening is the ability to identify and understand what others are saying. It is a first communicative skill that acquired for human being. It is an invisible mental process that plays a vital role in daily lives. People listen for different purposes such as entertainment, academic purposes or obtaining necessary information. Listening is the activity of paying attention to and trying to get a meaning from something we hear (Underwood, 1989). Listening as a part of transactional process in which all participants are simultaneously “sending” and “receiving” messages (Rost, 2002). Listening is an active process that not only what people hear but also how people connect it to other information they have already known (Helgesen in Nunan, 2003). There are some learner’s problems in Listening III at English Department Faculty of Education and Teacher Training State Institute for Islamic Studies Imam Bonjol Padang such as; lacks of control over the speed at which speakers speak, not being able to get thing repeated, the listener’s limited vocabulary, failure to recognize the “signals”, problems of interpretation, inability to concentrate, established learning habits. To solve the problem the writer use student’s work sheet adapted from Flowerdew (2005) with revision based on the students needs by watching movies. According to Norris (1193) Movies can be good authentic learning materials for listening skill because they contain dialogues from highly proficient English speakers which could contribute to an easier understanding of their pronunciation. It is stated that the students can get some benefits in watching films in English. They can improve their listening and speaking skills and they can enlarge their vocabulary knowledge and they can make their pronunciation and intonation better.